(untitled) - Hart, Jeffrey A (New York, 2004)
The advanced industrial countries considered replacing the existing analog television infrastructure with a new digital one in the late 1980s and 1990s. Jeffrey Hart's study demonstrates how nationalism and regionalism combined with conflicting ideas over technology to produce three different and incompatible DTV standards in the U.S., Japan and Europe. The outcome has led to missed opportunities in developing new technologies. Hart's work contributes to our understanding of relations between business and government, and of competition between the world's great economic powers.
Keywords: High definition television,High definition television,Truyền hình độ nét cao,High definition television |z United States,Truyền hình độ nét cao; Japan,Europe,Nhật Bản,Hoa Kỳ